Indonesia Suriname Tingkatkan Kerja Sama di Bidang Ekonomi - M. Agung Hidayah Nst; Tamaulina Br. Sembiring (PT. ALHAFI BERKAH INDONESIA, 2024)
This research aims to analyze the potential for increasing economic cooperation between Indonesia and Suriname, identify the challenges faced, and provide strategic recommendations to maximize bilateral collaboration. The phenomenon of increasing interest between the two countries to cooperate economically is the background for the research, with Suriname having a large Javanese community and historical ties with Indonesia, as well as efforts by both parties to look for opportunities to refresh and deepen economic ties. This research identifies that this economic cooperation provides opportunities for Indonesia to expand its export markets, establish technical cooperation, especially in agriculture and creative industries, and provide access for Suriname to wider investment and trade transactions with Asian markets. The results of the discussion show that in the economic sphere, there is a focus on increasing exports of several superior products from Indonesia and a commitment from the Indonesian private sector to continue to support cooperation in Suriname's infrastructure development, including port development projects and offshore oil exploration. From this study, the resulting recommendations suggest the governments of the two countries to facilitate cultural and educational exchanges as a bridge of understanding, harmonization of regulations, and development of better infrastructure.